Characterization of Control Methods for Fall Armyworm (Spodoptera frugiperda J. E. Smith) in the Maize (Zea mays L.) Cropping Systems in Central Benin - HOUNDETE, Codjo Jacques; ASSONGBA, Yedjanlognon Faustin; DJEGO, Julien Gaudence (My University, 2023)
In Benin, the Fall armyworm (Spodoptera frugiperda J.E. Smith) causes severe damage to maize crop and threatens the food security of thousands of small farmers. The objectif of this study was to inventory local knowledge on the management of the Fall armyworm (FAW) by maize farmers in central Benin. A semi-structured questionnaire was used to collect information from 1885 maize farmers in six communes in central Benin. Data were analyzed using descriptive statistics, multivariate analysis and logistic regressions. Results showed that farmers consider FAW attacks as a major constraint to maize production. The common control method used by maize farmers is chemical control (90% of respondents) with synthetic products. Chemical families such as Pyrethroids, Avermectins, Neonicotinoids, Organophosphates are used. The farmers (4%) use organic products such as aqueous extracts of Azadirachta indica, Jatropha curcas and Carica papaya to control FAW. Certain farmers do not used any control method for FAW. Socioeconomic characteristics such as area planted, age, experience in maize production, farmer’s organization membership, level of education, gender, and income level of the farmer significantly determine (p < 0.05) the type of control method used against FAW. These factors should be taken into account by extension programs. Extension services can use farmers in these socio-economic categories as innovators to spread new and more effective control methods against Fall armyworm.
Keywords: fall armyworm; insecticides; maize cropping system; farmer’s perception; Benin